2015
DOI: 10.1007/s11814-015-0128-5
|View full text |Cite
|
Sign up to set email alerts
|

Microbial bioremediation processes for radioactive waste

Abstract: Microbial processes can affect the environmental behavior of priority radionuclides, and understanding these reactions is essential for the safe management of radioactive wastes and can contribute to the remediation of radionuclide-contaminated land. Underlying mechanisms that can control radionuclide solubility in biogeochemical systems can range from biosorption and biomineralization process, through direct (enzymatic) and indirect redox transformations. The mechanisms of enzyme-mediated reduction of problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…[5][6][7] Currently, the growing interest in this species is to a large extent directed toward potential applications in biotechnology, such as remediation of soils and aquifers that have been contaminated with heavy metals or radionuclides, and a biocatalyst in microbial fuel cells. [7][8][9][10][11][12] S. oneidensis can grow not only aerobically, but also anaerobically with a variety of organic and inorganic substances as the terminal electron acceptor. This microbe has methylmenaquinone (MMK) besides UQ and MK, and the use of MK-minus mutants revealed that MK and/or MMK were required for the reduction of Fe(III), fumarate, and nitrate.…”
mentioning
confidence: 99%
“…[5][6][7] Currently, the growing interest in this species is to a large extent directed toward potential applications in biotechnology, such as remediation of soils and aquifers that have been contaminated with heavy metals or radionuclides, and a biocatalyst in microbial fuel cells. [7][8][9][10][11][12] S. oneidensis can grow not only aerobically, but also anaerobically with a variety of organic and inorganic substances as the terminal electron acceptor. This microbe has methylmenaquinone (MMK) besides UQ and MK, and the use of MK-minus mutants revealed that MK and/or MMK were required for the reduction of Fe(III), fumarate, and nitrate.…”
mentioning
confidence: 99%
“…Co-precipitation is another phenomenon where elements combine with metal oxide minerals during their precipitation [38] . Citrobacter and Serratia is are common example of biomineralization, which release phosphate ligand and form uranyl ions [52] . Table 4 summarized the mechanisms of radionuclide microbial bioremediation [53][54][55][56][57][58][59][60][61][62][63][64][65] .…”
Section: Biomineralization/bioprecipitationmentioning
confidence: 99%
“…In rhizofiltration, radionuclides are adsorbed and Figure 3. Various process involves in plant remediation of radionuclides [52] .…”
Section: Rhizofiltationmentioning
confidence: 99%
“…Facility and process engineering improvement (e.g., dry quenching and dry-dedusting techniques for blast furnaces and converter flue gas, comprehensive use of water, flue gas and all solid wastes, regenerative combustion technology, gas recycling technology, blast furnace top gas recoveryunit technology, sintering desulfurization, use of retorts, etc.) Red, Rec, O, L [29,35] Mine water recycling Rec, L [54,55] Mine water management Red, O [56,57] Bioremediation Red, E [58][59][60][61] Mine rehabilitation (e.g., progressive type) Red, R [55,62] Shift to renewable energy and decarbonization Red, R [63,64] Inter-enterprise (meso)…”
Section: Ce Layers Some Examples Of Technologies and Approaches Sourcesmentioning
confidence: 99%